(untitled) (Journal of Fatima Jinnah Medical University, 2018)
A retrospective study of 100 arthroscopy assisted acl reconstructions was carried out using metallic interference screws. The patients were followed up for a minimum of six months. There were associated meniscal injuries in 20 cases. There was one case of infection,5 cases of instability,6 cases of extension lag more than 5 degrees. In 3 cases flexion stayed less than 100 degrees. There was no incidence of fracture at the donor site. In 21 cases there was graft-tunnel mismatch. Functionally there was a good result in 61 cases.